Propuesta de una ruta cultural y el incremento del turismo interno en la ciudad de Iquitos – 2019 - Taminche Santillán, Liliana Tabita (2021)
The research has the purpose of determining if it is necessary to develop a cultural route to improve the internal tourism of the city of Iquitos during the year 2019, for this the sample design was carried out with a Population made up of the residents of the city and the visitors or tourists; As the population number is unknown, the formula of an infinite sample was applied to calculate the sample, being 96 people, of which 50% were city residents and 50% were visitors or tourists. The type of research was based on a quantitative, applied and cross-sectional model with a descriptive, non-experimental design that established the need to have a cultural route. For this, a desk study has been carried out to obtain historical data that addresses the theoretical framework and, the field work for the statistical calculation was from the data obtained as a result of the application of the data collection instrument, which was made up of 4 questions the general data and 28 questions or items of the Questionnaire. Finally, the objectives of the study have been determined, getting to know and determine the cultural manifestations, the expressions of folklore, the cultural activities and the motivations. The descriptive hypothesis has been demonstrated demonstrating the need to develop a cultural route, the guidelines of which are described in Annex 1.